PENGARUH KEPEMIMPINAN PROFETIK TERHADAP MUTU PENDIDIKAN DI MA’HAD ALY DAN MA’HAD AL JAMI’AH: SYSTEMATIC LITERATURE REVIEW - Jaswadi, Jaswadi; Muhajir, As’aril; Fitri, Agus Zaenul; Jabbar, Moch. Rikza Alkhubra Abdul; Nadir, Nadir (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2025)
This study examines the influence of prophetic leadership on educational quality in Islamic higher education institutions, specifically Ma'had Aly and Ma'had al-Jami'ah, using the Systematic Literature Review (SLR) method. Through an analysis of 26 articles published between 2015 and 2025, this study aims to answer three main questions: how is prophetic leadership conceptualized from an Islamic educational perspective, how it impacts educational quality, and effective implementation strategies. The results indicate that prophetic leadership, rooted in the values ??of shiddiq (belief), amanah (trustworthiness), tabligh (discipline), and fathanah (prophetic conduct), plays a crucial role in creating a spiritual atmosphere, shaping character, and strengthening a management system based on Islamic values. These values ??have been shown to improve academic and spiritual quality, discipline, and institutional loyalty. Identified best practices include exemplary leadership, the integration of prophetic values ??into the curriculum, spiritual training for educators, and the revitalization of values-based governance. This study emphasizes the importance of adopting a transformative and values-oriented leadership model in addressing the gap between the ideal goals of Islamic education and the reality on the ground. Theoretically, this study provides a conceptual synthesis linking prophetic leadership to improving educational quality. Practically, it provides strategic recommendations for institutional leaders. The findings also open up opportunities for further research that empirically tests the implementation of this model in a broader institutional context. Thus, prophetic leadership presents itself as a contextual, adaptive, and integrative leadership model to strengthen the quality assurance of Islamic education. ABSTRAKPenelitian ini mengkaji pengaruh kepemimpinan profetik terhadap mutu pendidikan pada lembaga pendidikan tinggi Islam, khususnya Ma’had Aly dan Ma’had al-Jami’ah, dengan menggunakan metode Systematic Literature Review (SLR). Melalui analisis terhadap 26 artikel yang diterbitkan dalam kurun waktu 2015–2025, kajian ini bertujuan menjawab tiga pertanyaan utama: bagaimana konsep kepemimpinan profetik dalam perspektif pendidikan Islam, bagaimana pengaruhnya terhadap mutu pendidikan, serta strategi implementasi yang efektif. Hasil penelitian menunjukkan bahwa kepemimpinan profetik yang berakar pada nilai shiddiq, amanah, tabligh, dan fathanah, memiliki peran penting dalam menciptakan atmosfer spiritual, membentuk karakter, dan menguatkan sistem manajemen yang berbasis nilai-nilai Islam. Nilai-nilai tersebut terbukti mampu meningkatkan kualitas akademik dan spiritual, kedisiplinan, serta loyalitas kelembagaan. Praktik terbaik yang teridentifikasi mencakup keteladanan pemimpin, integrasi nilai profetik dalam kurikulum, pelatihan ruhiyah bagi pendidik, serta revitalisasi tata kelola berbasis nilai. Kajian ini menekankan pentingnya adopsi model kepemimpinan yang transformatif dan berorientasi pada nilai dalam merespons kesenjangan antara tujuan pendidikan Islam yang ideal dan kenyataan di lapangan. Secara teoretis, studi ini menyusun sintesis konseptual yang menghubungkan kepemimpinan profetik dengan peningkatan mutu pendidikan. Secara praktis, kajian ini memberikan rekomendasi strategis bagi para pemimpin lembaga. Temuan ini juga membuka ruang untuk penelitian lanjutan yang menguji implementasi model ini secara empiris dalam konteks kelembagaan yang lebih luas. Dengan demikian, kepemimpinan profetik hadir sebagai model kepemimpinan yang kontekstual, adaptif, dan integratif untuk memperkuat penjaminan mutu pendidikan Islam.